The Dalai Lama and the Emperor of China : a political history of the Tibetan institution of reincarnation - Schwieger, Peter (Columbia University Press, 2014)
A major new work in modern Tibetan history, this book follows the evolution of Tibetan Buddhism's trülku (reincarnation) tradition from the seventeenth to the nineteenth centuries, along with the Emperor of China's efforts to control its development. By illuminating the political aspects of the trülku institution, Schwieger shapes a broader history of the relationship between the Dalai Lama and the Emperor of China, as well as a richer understanding of the Qing Dynasty as an inner Asian empire, the modern fate of the Mongol empire, and current Sino-Tibetan relations. Unlike other pre-twentie.